Vegetation diversity and its interspecies association with merbau (Intsia bijuga) at three habitats of tropical rain forest in West Papua, Indonesia - Susanti Tasik; SITI MUSLIMAH WIDYASTUTI; MUSYAFA MUSYAFA; PRIYONO SURYANTO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Tasik S, Widyastuti SM, Musyafa, Suryanto P. 2021. Vegetation diversity and its interspecies association with merbau (Intsia bijuga) at three habitats of tropical rain forest in West Papua, Indonesia. Biodiversitas 22: 3383-3391. The stability of vegetation community indicated by species diversity, structure and composition affects the relationship between species. The understanding of interspecies association in their natural habitat is important especially for management and conservation strategies of species with particular interest, including merbau (Intsia bijuga O. Colebr Kuntze), a timber tree species with high commercial value. This study aims to investigate the diversity and composition of vegetation coexisting with merbau, and to see whether there is pattern of interspecies association with merbau. Vegetation analyses of species richness, diversity index, evenness index and interspecies relationship were conducted at three research locations in West Papua, Indonesia, namely Mount Meja Natural Tourism Park (Hutan Taman Wisata Alam Gunung Meja/HTWAGM), Bembab Beach Forest of South Manokwari (Hutan Bembab Pantai Manokwari Selatan/HBPMS) and Bembab Mountain Forest of South Manokwari (Hutan Bembab Gunung Manokwari Selatan/HBGMS). The results showed that the species Caryota rumphiana, Licuala sp 1, Calophyllum inophyllum, Garcinia pichoriza, Pometia coreacea and Pometia pinnata always grew side by side with Intsia bijuga in three locations. Furthermore, the association analysis indicated a positive and strong relationship between Intsia bijuga and Pometia coreacea, Licuala sp1, Licuala sp 2, Caryota rumphiana at all three research sites. In addition, Pometia coracea had the highest Chi-square value (X2 = 20.00) with the value of the three association indexes reached maximum value. We also found that the vegetation communities in the habitat of merbau had varying vegetation structure and composition as well as biodiversity indicators, yet they were all at stable state. The finding on vegetation analyses was confirmed with the result of soil analyses in which the physical and chemical properties had optimal conditions for vegetation to grow, including for merbau.